2015
DOI: 10.1016/j.mattod.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of multi-directional preforms for composites: opportunities and challenges

Abstract: Current additive manufacturing methods present the potential to construct net-shape structures with complicated architectures, thus eliminating the need for multi-step processing and fasteners/joints. Combined with these features is the ability to ascribe material properties at the sub-millimeter scale, inspiring multi-material, functionally graded designs. These features make additive manufacturing an attractive option for composite materials development. In an effort to extend this family of technologies bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(122 citation statements)
references
References 61 publications
2
110
0
3
Order By: Relevance
“…A marriage of nanomaterials and 3D printing could offer clear advantages and numerous new opportunities [18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…A marriage of nanomaterials and 3D printing could offer clear advantages and numerous new opportunities [18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…The choice of the composite formation generally depends on the types of printing systems; however, both approaches are capable of delivering distinct physicochemical properties into the resultant materials . This domain of composite printing is presenting a combination of superior technologies and material systems with an immense potential, affordability, simplicity, and unaccountable advantages . Table describes the recent applications of 3DP systems for different end‐user applications by utilizing PMC systems.…”
Section: Dp Technologies For Pmc Systemsmentioning
confidence: 99%
“…Four types of specimens as shown in Table 1 were additively manufactured using fused filament fabrication approach [30,31]. The structural parameters were depicted in Fig.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…In order to explore opportunities for additive manufacturing of multidirectional preforms for composites, Quan et al recently demonstrated the fabrication of an array of preforms via fused filament fabrication (FFF) [30] and reported their results on microstructural design and additive manufacturing and characterization of short carbon fiber/acrylonitrile-butadiene-styrene (ABS) 3D orthogonal preforms and composites [31]. Although high model-to-part fidelity was observed, the microstructure and interfaces of additively manufactured preforms and composites were not characterized.…”
Section: Introductionmentioning
confidence: 99%